The chemical structure and immunomodulatory activity of an exopolysaccharide produced by Morchella esculenta under submerged fermentation. Issue 19 (24th August 2021) - Li, Jinglei; Wu, Haishan; Liu, Yuting; Nan, Jian; Park, Hyun Jin; Chen, Yanping; Yang, Liu
Abstract : Chemical structure and immunomodulatory activity of an exopolysaccharide produced by Morchella esculenta. Abstract : The extracellular polysaccharide of Morchella esculenta cultivated under submerged fermentation was extracted. A single polysaccharide was purified through DEAE-Cellulose 52 and Sephadex G 100, and named as MEP 2a. The molecular weight of MEP 2a was determined by HPGPC and it is about 1391.5 kDa. MEP 2a is composed of mannose and glucose as the monosaccharide unit with a molar ratio of 8.15 : 1.07. The main polysaccharide chemical structure was analyzed by 1D and 2D NMR. Methylation and NMR analysis revealed that the backbone of MEP 2a consists of 1, 3, 4-linked-Manp, 1, 2-linked-Manp and 1, 6-linked-Glcp. 1D and 2D NMR results indicated that the main chain is based on →1)-β-d -Glcp-(6→, →1)-α-d -Manp-(3, 4→, →1)-α-d -Manp-(2→) and the branch chain is composed of α-d -Manp-(1→, →1)-β-d -Glcp-(6→ and α-d -Glcp-(1→). MEP 2a promoted the phagocytosis function and secretion of NO, IL-1β, IL-6 and TNF-α of macrophages. In the present study, the chemical structure and immunomodulatory ability of an extracellular polysaccharide of Morchella esculenta was investigated which guarantees further research studies and promising applications.